Sensory–Cognitive Profiles in Children with ADHD: Exploring Perceptual–Motor, Auditory, and Oculomotor Function - Danjela Ibrahimi; Marcos Aviles; Rafael Rojas-Galván; Juvenal Rodríguez Reséndiz (Bioengineering, 2025)
Objective: This observational cross-sectional study aimed to comprehensively evaluate sensory–cognitive performance in children diagnosed with Attention-Deficit/Hyperactivity Disorder (ADHD), with a focus on auditory processing, visual–perceptual abilities, visual–motor integration, and oculomotor function. The study further examined how hyperactivity, age, and gender may influence these domains. Methods: A total of 70 non-medicated children with clinically diagnosed ADHD (mean age = <semantics>9.1±2.4</semantics> years; 67.1% male), all with normal visual acuity, were assessed using four standardized instruments: the Test of Auditory Processing Skills, Third Edition (TAPS-3), the Test of Visual Perceptual Skills, Fourth Edition (TVPS-4), the Beery–Buktenica Developmental Test of Visual–Motor Integration, Sixth Edition (VMI-6), and the Developmental Eye Movement (DEM) Test. Statistical analyses included one sample and independent samples t-tests, one-way ANOVA, and Pearson correlation coefficients. Results: Participants demonstrated significantly above-average performance in auditory processing (TAPS-3: <semantics>μ=108.4</semantics>, <semantics>std=7.8</semantics>), average visual–perceptual abilities (TVPS-4: <semantics>μ=100.9</semantics>, <semantics>std=7.2</semantics>), slightly below-average visual–motor integration (VMI-6: <semantics>μ=97.1</semantics>, <semantics>std=9.0</semantics>), and marked deficits in oculomotor efficiency (DEM ratio: <semantics>μ=87.3</semantics>, <semantics>std=18.1</semantics>). Statistically significant differences were observed across these domains (t-values ranging from 2.9 to 7.2, <semantics>p<0.01</semantics>). Children with hyperactive-impulsive presentations exhibited lower horizontal DEM scores (<semantics>μ=73.4</semantics>, <semantics>std=12.3</semantics>) compared to inattentive counterparts (<semantics>μ=82.9</semantics>, <semantics>std=16.2</semantics>; <semantics>p=0.009</semantics>). Age and sex influenced specific subtest scores, with boys and children aged 8–9 years achieving higher outcomes in word memory (<semantics>p=0.042</semantics>) and visual discrimination (<semantics>p=0.034</semantics>), respectively. Moderate correlations were identified between auditory and visual–perceptual skills (<semantics>r=0.32</semantics>, <semantics>p=0.007</semantics>), and between visual–perceptual and oculomotor performance (<semantics>r=0.25</semantics>, <semantics>p=0.035</semantics>). Conclusions: The findings from this sample reveal a distinct sensory–cognitive profile in children with ADHD, characterized by relatively preserved auditory processing and pronounced oculomotor deficits. These results underscore the value of a multimodal assessment protocol that includes oculomotor and visual efficiency evaluations. The conclusions pertain specifically to the cohort studied and should not be generalized to all populations with ADHD without further validation.